Interacción socio afectiva de niños con síndrome de Down - Santo Arequipa, Mayra Marcela (2020)
The present investigation aims to strengthen the socio-emotional relationship of children with Down syndrome from the “Marco Aurelio Subía M – Batalla de Panupali” School, through active strategies to improve their social and emotional relationships with other people since it showed that they have problems to interact with others, they react with anger when someone corrects them, they a quite participation in group activities, they ignore and disrespect basic rules when working in teams, they show emotional disturbances such as anger and frustration. The research methodology that was used was qualitative, descriptive and bibliographic research was also used which was guided by the inductive method. The information gathering techniques such as the survey of authorities, teachers, parents, reflected that there are difficulties for children to interact socially and emotionally. All these inputs have served to elaborate the proposal “Guide of active strategies for the socio-affective development of children with Down syndrome” that consists of 17 activities to be developed. The proposal was validated through two instruments (the user criterion and the socialization workshop), which resulted in an arithmetic average of 4.67 and favorable opinions that demonstrate its feasibility and feasibility.